A Feasibility Study of Acupuncture for Chronic Pain in Patients with Osteoporotic Thoracolumbar Compression Fracture: A Prospective Case Series - Ji min Bae; Ji won Choi; Dae hun Kim; Gi Young Yang; Kun hyung Kim (MEDrang Inc., 2018)
Background The aim of this study was to assess the feasibility of conducting a clinical study of using acupuncture for chronic pain in patients with osteoporotic thoracolumbar vertebral compression fractures(VCFs) in the outpatient setting. Methods A prospective case-series attempting to recruit 20 participants was performed from February 11, 2016, to December 31, 2016. We provided Manual and electrical acupuncture was provided one 1 to three 3 times a week, for 6 weeks, up to 18 sessions. The primary clinical outcome was the average pain intensity as measured by the visual analog scale (VAS) at 6 weeks. Secondary outcomes included back-specific dysfunction (Oswestry disability index), quality of life (quality of life questionnaire-26), patient-reported improvement, use of other healthcare resources, and adverse events at 6 weeks. Use of healthcare resources and adverse events were additionally followed-up at 12 weeks by telephone. Results Of 33 patients screened, a total of 7 were enrolled in the study. Manual and electrical acupuncture was provided 1 to 3 times a week, for 6 weeks, up to 18 sessions. We observed reduced pain intensity at 6 weeks in all participants. The change in the quality of life and back-specific dysfunction was inconsistent among participants. Mild, temporary adverse events were observed in three patients. Conclusions In our clinical setting, it was not feasible to recruit sufficient participants and to assess the efficacy of acupuncture for chronic pain after osteoporotic thoracolumbar VCFs under a year. Strategies to improve recruitment and to identify barriers to participation are required for future clinical trials.